2016
DOI: 10.4172/2161-1165.1000281
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Temperature for Malaria Transmission in Gongi Kolela District, Amhara Regional State, North West Ethiopia

Abstract: Background: Malaria is a disease caused by protozoan parasites of the genus Plasmodium and transmitted by the bite of infected female anopheles mosquitoes. Temperature have influential role for malaria transmission. This study was done to see the correlation between positive malaria cases and temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, an increase in temperatures does not mean an increase in malaria transmission if accompanied by a decrease in rainfall, since lack of water prevents development of the vector. At low temperatures, the vector needs to survive longer for the saprogenic cycle to take place, while temperatures above 30°C counteracts mosquito survival (Mordecai et al, 2013;Brhanie, 2016) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, an increase in temperatures does not mean an increase in malaria transmission if accompanied by a decrease in rainfall, since lack of water prevents development of the vector. At low temperatures, the vector needs to survive longer for the saprogenic cycle to take place, while temperatures above 30°C counteracts mosquito survival (Mordecai et al, 2013;Brhanie, 2016) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We mapped the malaria hazard using the ArcGIS raster calculator taking into account related previous work, national malaria guidelines, available reports (FMoH, 2008(FMoH, , 2014 and the different environmental factors as these factors would modulate the core hazard (presence of a malaria case together with capable vectors). Special reference was paid to the temperature as it not only governs vector capability, but also the parasite's requirement inside the vector (Mordecai, 2013;Brhanie, 2016).…”
Section: Variables Investigatedmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegetation may provide an outdoor resting habitant or shelter for mosquitoes from extreme conditions unfavourable for mosquito-population growth. Many studies have reported associations between changes in malaria burden and patterns of environmental factors [7][8][9][10][11][12][13]. However, the associations reported vary between settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, the associations reported vary between settings. For example, a study from South Africa found that an increase in temperature signi cantly raised malaria infections [12], while another in Ethiopia showed a negative correlation [13].…”
Section: Introductionmentioning
confidence: 99%